People matter: commitment to employees, strategy and performance in Korean firms - Lee, Jangwoo; Miller, Danny (Strategic Management Journal, 1999)
The human element of enterprise is argued to be a vital resource for strategy execution. We show in a study of Korean businesses how an organization’s commitment to its employees’ well-being (OCE) can aid in the profitable execution of its positioning strategies. We found that OCE, by itself, sometimes has a weakly positive association with return on assets (ROA). But far more important, we found that ROA is strongly and positively influenced by the interaction between OCE and the dedicated pursuit of Porter’s (1980) strategies for achieving competitive advantage: these are cost leadership, marketing differentiation and innovative differentiation. In short, dedicated positioning strategies appear to be executed more effectively where organizations exhibit a high level of commitment to their employees; and conversely, OCE is apt to have a strong impact on ROA only in the context of a dedicated, that is intensive and thorough, positioning strategy. Copyright © 1999 John Wiley & Sons, Ltd.